Government led innovations in affordable housing delivery - Rowley, Steven; James, Amity; Phibbs, P.; Troy, L.; van den Nouwelant, R. (Australian Housing and Urban Research Institute Limited Melbourne, Australia, 2018)
This project examined state government-led innovations in affordable housing through analysis of two state-level strategies (the Western Australian Affordable Housing Strategy and the ACT Affordable Housing Action Plan and two state-level programs (the NSW Asset Vesting Program and the East Kimberley Transitional Housing Program).